Budaya Kerja Kepolisian Dalam Pelayanan Masyarakat Di Polsek Rappocini Makassar - Setiawan, Anggi; Malik, Ihyani; Nasrulhaq, Nasrulhaq (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed to determine the work culture of the police in serving the community, satisfaction, accuracy of targets in its implementation and public services to the community. This study used qualitative with 5 informants. Data collection techniques were in-depth interviews, direct observation, documentation. The results of this study showed that the habits of Rappocini police officers in providing excellent service to the community by using local / regional culture and community trust. Every arrangement in the agency  or private prioritized or improved the family system. In improving performance that was appropriate, fast and professional, Rappocini Police Sector Regulations  that provided public services to the community in order to provide maximum service, guided by tri brata and Catur prasetya  and the commission of the police profession code of ethics as the main task of the police to protect, serve and enforce the law, as well as Values in the view of the Makassar Rappocini Police Sector in providing services to the community in accordance with the reality that had not been running optimally. The application of perfomance had not  run well, convoluted service, acts of favoritism or exceptions.